Heyde's syndrome - Perišić Nenad; Doder Radoje; Ilić Radoje; Jović Jasna; Tukić Ljiljana; Tavčiovski Dragan (Vojnosanitetski Pregled)
Background: Heyde's syndrome implies an association of calcified aortic stenosis with the high gradient of pressure and angiodysplasic bleeding from the digestive tract. It has been proven that in patients with this syndrome, acquired form of von Willebrand type II A develops. Replacing of aortic valves by artificial ones brings about the spontaneous retreat of coagulation disorder, and the stoppage of the digestive tract bleeding. Case report. We reported two patients with the Heyde's syndrome. In one of the patients the aortic valves were replaced by biologic valves, after which the digestive tract bleeding stopped, while the second patient was treated conservatively due to a high operation risk. Conclusion. Patients with Heyde's syndrome are a complex multidisciplinary problem, thus their adequate treatment requires a team work in order to provide the most rational type of therapy for each patient separately.